(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2015)
The Italian Supreme Court, with its judgement no. 15138/2015, allowed a transsexual person – who had undergone male-to-female hormone replacement therapy and surgery on secondary sex characteristics but not SRS – to change her sex, because her MtF process has been judged completed and irreversible. This decision solved a long conflict of case-law, protecting the right to gender identity and the right to health (and declaring that the interest about the certainty of genders and juridical relatonships is not at risk, because transsexualism is not a so spread phenomenon).